Good Kurds, Bad Kurds: No Friends but the Mountains - Mckiernan, Kevin (United States : Access Production, Kevin McKiernan, 2000)
With a population of 25 million spilling across the borders of Turkey, Iraq, Iran, Syria and the former Soviet Union, the Kurds have maintained their way of life for more than 2,000 years, despite attempts by various empires and nation states to eradicate their culture. Forbidden in Turkey to speak their own language, to sing their own songs, even to call their children by Kurdish names, the Kurds for generations have struggled to preserve their identity and to foster their traditions. In the early nineties, the Kurds of nearby Iraq found themselves suddenly supported in their old war for independence against Baghdad, when their interests coincided with those of Western powers fighting against Saddam Hussein. In contrast, Kurds living across the border in Turkey, waging a similar battle for survival, were not supported in their uprising against Turkey, a vital American ally with bases for U.S. This film brings into sharp focus U.S. human rights and a foreign policy with different rules for different people. It provides the perspectives of Turkish, U.S. and European officials, as well as human rights representatives, and it includes exclusive footage shot behind the lines of Kurdish guerrillas in Iraq and Turkey.
Soros Documentary Fund
Soros Documentary Fund
Keywords: Documentary films